1985
DOI: 10.1128/mcb.5.4.869
|View full text |Cite
|
Sign up to set email alerts
|

Circular and linear simian virus 40 DNAs differ in recombination.

Abstract: Linear forms of simian virus 40 (SV40) DNA, when added to transfection mixtures containing circular SV40 and +X174 RFI DNAs, enhanced the frequency of SV40/+X174 recombination, as measured by infectious center in situ plaque hybridization in monkey BSC-1 cells. The sequences required for the enhancement of recombination by linear DNA reside within the SV40 replication origin/regulatory region (nucleotides 5,171 to 5,243/0 to 128). Linearization of +X174 RFI DNA did not increase the recombination frequency. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 51 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…Replication proceeds bidirectionally, similar to theta replication, and leads to two interlinked DNA circles, which are resolved through the action of topoisomerases I and II (reference 360 and references therein). It has been proposed that linear SV40 genomes can initiate rolling-circle replication, generating concatemers, and that this method of replication may explain some of the recombination seen in viral variants (105,122,459).…”
Section: Replication Of Jcv Genomic Dnamentioning
confidence: 99%
“…Replication proceeds bidirectionally, similar to theta replication, and leads to two interlinked DNA circles, which are resolved through the action of topoisomerases I and II (reference 360 and references therein). It has been proposed that linear SV40 genomes can initiate rolling-circle replication, generating concatemers, and that this method of replication may explain some of the recombination seen in viral variants (105,122,459).…”
Section: Replication Of Jcv Genomic Dnamentioning
confidence: 99%
“…We believe that the effect observed when RmI is cut is probably due to another parameter, such as the replicative state of the molecule at the time of recombination. We and others have shown that replication has an influence on the nature and frequency of recombination (9,51). Why did double-strand breaks not increase the ratio of homologous to nonhomologous recombination?…”
mentioning
confidence: 99%
“…We have documented elsewhere that origin-containing (ori+) linear forms of simian virus 40 (SV40) DNA, when added to transfection mixtures containing circular SV40 and 4X174 replicative form I DNAs, enhance the frequency of SV4O/4X174 recombination as measured by infectiouscenter in situ plaque hybridization in monkey BSC-1 cells (4). A key structural feature of such recombinants is the interspersion of 4X174 DNA within tandem head-to-tail repeats of sequences derived from the ori+ linear SV40 DNA.…”
mentioning
confidence: 99%
“…It was also shown that the tandem repeats are generated by a replication-related process rather than by homologous recombination. To account for these findings, we postulated that the recombination-enhancing properties of linear SV40 ori+ DNA are associated with the entry of that DNA into a rolling-circle type of replication which generates recombinogenic intermediates (4). The proposed model envisages that 4X174 replicative form I DNA recombines with the circular template of the intermediate (5) such that continuation of rolling-circle replication generates tandemly repeated segments containing both SV40 ori+ and 4~X174 DNAs.…”
mentioning
confidence: 99%